Learning from construction failures : applied forensic engineering - Campbell, Peter, 1949- (Whittles, 2001)
In the developed world the design and construction of all aspects of the built environment are regulated by rules and procedures which help prevent failures. When compared to the volume of construction undertaken, the number of failures of buildings and other structures is thankfully small. However, this reality is not reflected on a global basis. Failures do occur, some making headline news, and for a variety of reasons. As such information about failures is vital to make construction even safer.